The effect of fetal calf serum on human dental pulp stem cells - Suchánek, Jakub; Kleplová, Tereza Suchánková; Kapitán, Martin; Soukup, Tomás (Acta medica (Hradec Kralove), 2013)
AIMS: Authors studied potential side effects of fetal calf serum (FCS) in cultivation media on human dental pulp stem cells (DPSC) during long-term cultivation. METHODS: Two lines of DPSC obtained healthy donors (male 22 years, female 23 years) were used. Both lines were cultivated under standard cultivation conditions in four different media containing 10% or 2% FCS and substituted with growth factors. During long-term cultivation proliferation ability, karyotype and phenotype of DPSC were measured. RESULTS: Both lines of DPSC cultivated in a media containing 2% FCS and ITS supplement showed the highest number of population doublings. On the other hand the proliferation rate of DPSC cultivated in a media with 2% FCS without ITS supplement was slowest. Proliferation rate of DPSC cultivated in 10% FCS media with or without FGF-2 was comparable. DPSC cultivated in a media with 10% FCS showed a significantly higher amount of chromosomal aberrations. These chromosomal aberrations do not seem to be clonal but surprisingly we found large amounts of tetraploid cells in the 9th passage in both media containing 10% FCS. CONCLUSIONS: Our study proved that cultivation of DPSC in media containing higher concentration of FCS has critical side effects on cell chromosomal stability.
Keywords: Humans; Female; mladý dospělý; lidé; zvířata; proliferace buněk; Cells, Cultured; Fetal Blood; Stem Cells; Cattle; ženské pohlaví; fetální krev; Male; Dental Pulp; kultivované buňky; Cell Proliferation; skot; Young Adult; kmenové buňky; Animals; zubní dřeň; mužské pohlaví